Analisis strategi pertumbuhan bank syariah melalui teknologi digital di indonesia - santoso, muhammad irham imam (Maliki Interdisciplinary Journal, 2025)
The advancement of digital technology has significantly influenced the global financial system, including Islamic banking in Indonesia. Digital transformation has become not only a necessity but also a strategic instrument to promote growth, efficiency, and competitiveness in the Islamic financial industry. This research adopts a literature review approach by analyzing recent academic journals and reports on digitalization in Islamic banking. The findings show that digitalization plays an essential role in improving service quality, financial inclusion, and operational efficiency. However, challenges such as low digital literacy, data security, and compliance with sharia principles remain. Collaboration among banks, regulators, and the public is essential to ensure that the digital transformation proceeds sustainably and in line with Islamic values.